PEEP titration during prone positioning for acute respiratory distress syndrome. Issue 1 (December 2015) - Beitler, Jeremy; Guérin, Claude; Ayzac, Louis; Mancebo, Jordi; Bates, Dina; Malhotra, Atul; Talmor, Daniel
Abstract No major trial evaluating prone positioning for acute respiratory distress syndrome (ARDS) has incorporated a high-positive end-expiratory pressure (high-PEEP) strategy despite complementary physiological rationales. We evaluated generalizability of three recent proning trials to patients receiving a high-PEEP strategy. All trials employed a relatively low-PEEP strategy. After protocol ventilator settings were initiated and the patient was positioned per treatment assignment, post-intervention PEEP was not more than 5 cm H2 O in 16.7 % and not more than 10 cm H2 O in 66.0 % of patients. Post-intervention PEEP would have been nearly twice the set PEEP had a high-PEEP strategy been employed. Use of either proning or high-PEEP likely improves survival in moderate-severe ARDS; the role for both concomitantly remains unknown.